Cross‐linked gelatin microspheres with continuously tunable degradation profiles for renal tissue regeneration. (22nd October 2013) - Serban, Monica A.; Knight, Toyin; Payne, Richard G.; Basu, Joydeep; Rivera, Elias A.; Robbins, Neil; McCoy, Darell; Halberstadt, Craig; Jain, Deepak; Bertram, Timothy A.
Abstract Collagen and gelatin‐based biomaterials are widely used in tissue engineering applications. Various methods have been reported for the cross‐linking of these macromolecules for the purpose of delaying their biodegradation to prolong their in vivo residence (in tissue engineering applications) or tailoring their drug releasing capacity (when used as drug carriers). In this study, a carbodiimide‐based cross‐linking method, also used in the production of United States Food and Drug Administration‐approved products, was employed to obtain differentially cross‐linked gelatin beads. The colorimetric determination of the in vitro enzymatic susceptibility of the beads indicated that the resistance to degradation linearly correlated with the concentration of carbodiimide used for the cross‐linking reaction. This result was also confirmed in vivo by the histological evaluation of the residence time of orthotopically injected cell‐seeded beads. These data would indicate that the production of gelatin‐based microbeads with tunable degradation profiles might be applicable toward the development of products that catalyze regeneration of kidney and other solid organs.